(untitled) (Research, Society and Development, 2020)
Pulmonary disorders are major causes of death in the world population, with obstructive ventilatory disorders (OVD) being one of its types, which can generate chronic airflow obstruction that is not fully reversible. This study aimed to analyze deaths due to obstructive disorders in adults and the elderly in the State of Ceará between the years 2015 to 2019. This is an epidemiological, cross-sectional, quantitative study, consisting of data from individuals of both sexes, as reported in DataSUS , adopting young people, adults and the elderly as inclusion criteria, following the values ​​of the age group of the Brazilian population provided by the IBGE (20 to 80 years or more), these being delimited to the group of patients who had died from OVD and who had entered in any Hospital Unit in the state of Ceará in the last 5 years (2015-2019). As a result, it was possible to observe an increase in the number of deaths in females, over 70 years of age, with an emphasis on the year 2017, with a decrease in subsequent years. The pathology with the highest number of deaths was COPD, which affected the female sex the most, and the least affected Bronchiectasis, with the male sex being the most affected. In this study, it was possible to see that deaths from OVD increased with increasing age, with an emphasis on the year 2017 and among women, and which pathologies lead to death more frequently, enabling the search for strategies that prevent the increase in the number of cases of these diseases.